Oviposition Site Preference for Natural Breeding Sites in Drosophila melanogaster (Diptera: Drosophilidae) Populations From Argentina - Betti, María Isabel Luján (2014)
Maternal decisions, like the choice of a site for laying eggs, have important ecological and evolutionary implications. In the current study, we investigated variation both within and between populations in oviposition site preference (OSP) in a collection of isofemale lines derived from three Drosophila melanogaster Meigen natural populations of western Argentina. In the oviposition preference assay, we used two resources that fruit ßies use as egg-laying sites in nature. Results revealed 1) the distribution of eggs across the two alternative resources offered to the ßies deviated from random when ßies were given the chance to choose between grape and orange, 2) OSP varied within and between populations, and 3) a substantial proportion of OSP variation has a genetic basis as suggested by the signiÞcant contribution of variation among lines to total trait variance. Our survey represents an initial step in understanding patterns of natural variation in oviposition preferences for natural resources in D. melanogaster.